Baralaga keeping alive our indigenous values. (The Philippine Task Force for Indigenous People's Rights(TFIP), 2011)
This video, in collaboration with Tan-aw Multi-media Collective, presents a documentary on the indigenous values of indigenous peoples that teach good relations among the people and harmony with the environment.